Design Extractor Machine Untuk Meningkatkan Kualitas Dan Kuantitas Produksi Syrup Nira Tebu Sebagai Pemanis Pengganti Gula Pasir - Rina Rifqie Mariana; Gunawan, Aditia Gustiana; Nada Itorul Umam; Andoko; Yoto (Ilin Institute, 2025)
This community service activity is an implementation of the 2022 research findings, which revealed that sugarcane sap, as a raw material for granulated sugar, contains antioxidants beneficial for health. Various sugarcane sap-based products have been introduced to the community, particularly to SMEs and sugarcane farmers in Pagelaran Village. The community’s response has been very positive, as sugarcane is a local commodity in the village. However, a challenge faced in the 2023 community service project was the unavailability of a sugarcane sap extractor, forcing them to buy sugarcane sap from outside the village. This approach was inefficient, and the sap easily spoiled due to microbial activity, leading to the breakdown of sucrose into reducing sugars and other compounds. To address this, the team designed and built a sugarcane sap extractor machine and provided training on making flavored sugarcane syrup. The event took place on September 19, 2024, with 28 participants from SMEs and farmers’ groups, along with 7 village officials. The participants were taught how to use the extractor, how to make sugarcane syrup, the benefits of the syrup, product branding, and basic bookkeeping. At the end of the session, the machine was handed over to the village head to be donated to the SMEs as capital for producing functional drinks from sugarcane sap. The participants responded positively, and the SMEs committed to expanding their business by offering functional drinks made from sugarcane sap, including sugarcane syrup in various flavors.